2015
DOI: 10.3892/mmr.2015.4330
|View full text |Cite
|
Sign up to set email alerts
|

Differential microRNA expression in aristolochic acid-induced upper urothelial tract cancers ex vivo

Abstract: Aristolochic acid (AA) is a carcinogenic, mutagenic and nephrotoxic compound commonly isolated from members of the plant family of Aristolochiaceae (such as Aristolochia and Asarum) and used in Chinese herbal medicine. Use of AA and AA-containing plants causes chronic kidney disease (CKD) and upper urinary tract carcinoma (UUC); however, the underlying mechanism remains to be defined. miRNAs regulate a number of biological processes, including cell proliferation, differentiation and metabolism. This study expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 52 publications
1
28
0
Order By: Relevance
“…Recently a few studies that investigated microRNA profile in nephropathies caused by aristolochic acid in humans and rats have been published [ 56 58 ]. Tao et al [ 57 ] compared the expression of microRNA in aristolochic acid nephropathy-UTUC tissues (AAN-UTUC) and non-AAN-UTUC tissues in order to identify the unique gene alterations for AAN-UTUC. They have found 29 differentially expressed microRNAs; the eight most significantly expressed microRNAs are hsa-miR-4795-5p ↓, hsa-miR-488 ↑, hsa-miR-4784 ↓, hsa-miR-330 ↓, hsa-miR-3916 ↓, hsa-miR-4274 ↑, hsa-miR-181c ↓, and hsa-miR-4434 ↑.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently a few studies that investigated microRNA profile in nephropathies caused by aristolochic acid in humans and rats have been published [ 56 58 ]. Tao et al [ 57 ] compared the expression of microRNA in aristolochic acid nephropathy-UTUC tissues (AAN-UTUC) and non-AAN-UTUC tissues in order to identify the unique gene alterations for AAN-UTUC. They have found 29 differentially expressed microRNAs; the eight most significantly expressed microRNAs are hsa-miR-4795-5p ↓, hsa-miR-488 ↑, hsa-miR-4784 ↓, hsa-miR-330 ↓, hsa-miR-3916 ↓, hsa-miR-4274 ↑, hsa-miR-181c ↓, and hsa-miR-4434 ↑.…”
Section: Discussionmentioning
confidence: 99%
“…The small number of patients analyzed both in our study and in the study by Tao et al might be responsible for the difference. Furthermore, we have analyzed the differentially expressed microRNAs in BEN-UTUC and non-BEN-UTUC, both versus normal tissue in order to define microRNAs that could be a signature for BEN-UTUC patients, while Tao et al [ 57 ] investigated expression of microRNA in AAN-UTUC versus non-AAN-UTUC tissues. Also, the flow of disease and the duration of its development differ between BEN and AAN (Chinese herb nephropathy), which occurs more rapidly.…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, Asarum contains Aristolochene [ 25 , 26 ], which exists broadly in Aristolochia plants, and showed extremely strong oncogenic [ 27 ], mutagenic, [ 28 ] and renal toxicity [ 13 , 29 , 30 ]. Sarisan can lead to carcinogenesis through liver metabolism [ 19 ] and respiratory disorders by inhibiting nerve transfer in medullary the neural networks [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…MMPs are ion-active proteases that are ubiquitous in the cartilage and function to degenerate chondrocytes and degrade the extracellular matrix in the cartilage ( 9 11 ). MicroRNAs (miRNAs) are single-stranded non-coding RNAs that are associated with the development and progression of OA ( 12 ). It has been reported that miRNAs serve a role in the pathogenesis of OA regulating the expression of inflammatory mediators, vascular endothelial growth factor and nerve growth factor ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are single-stranded non-coding RNAs that are associated with the development and progression of OA ( 12 ). It has been reported that miRNAs serve a role in the pathogenesis of OA regulating the expression of inflammatory mediators, vascular endothelial growth factor and nerve growth factor ( 12 ). Further studies have revealed that miRNAs may inhibit or promote the expression of MMPs and collagen, resulting in the degeneration of chondrocytes and cartilage extracellular matrix, eventually leading to OA ( 13 , 14 ).…”
Section: Introductionmentioning
confidence: 99%